593 Efficacy of invariant natural killer T cell infusion plus transarterial embolization vs transarterial embolization alone for hepatocellular carcinoma patients: a phase 2 randomized clinical trial - Guo, Jia; Bao, Xuli; Liu, Fuquan; Guo, Jiang; Wu, Yifan; Xiong, Fang; Lu, Jun (Journal for immunotherapy of cancer, 2023)
BackgroundHepatocellular carcinoma remains a leading cause of mortality worldwide, accounting for over three quarter of a million deaths annually.1 While transarterial chemoembolization (TACE) therapy is the current first-line intervention for the roughly 70–80% of cases which are non-resectable,2–6 repeated treatments quickly lead to recalcitrance in recurring tumors, and 5-year survival rates linger at an abysmal 18%.7 The results of our phase 1 trial indicated that autologous iNKT cell therapy has good tolerability in HCC patients and could potentially further improve outcomes.8 MethodsThis randomized, multicenter, open-label phase 2 trial was conducted at Beijing Youan, Beijing Shijitan, and Beijing Ditan Hospital of Capital Medical University between March 2018 and March 2020.Follow-up was completed on July 20, 2020. The cohort comprised 54 Barcelona Clinic Liver Cancer (BCLC) B/C stage patients with HCC after TACE failure. Efficacy analyses were conducted in the modified intention-to-treat population. Eligible patients were randomly assigned (1:1) to receive either transarterial embolization (TAE) therapy (TAE group) or a combination of TAE (weeks 0 and 4) plus iNKT cell infusion (6~9×107 cells/m2 intravenously) every 2 weeks starting week 1 (TAE-iNKT group). To exclude compromising iNKT cells, TAE was used instead of TACE. The primary endpoint was PFS. Secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), quality of life (QoL), peripheral blood cell count, and safety.ResultsFifty-four patients completed the study (table 1). Median PFS was significantly higher in TAE-iNKT patients (5.7 months [95% CI, 4.3–7.0 months]) compared with TAE patients (2.7 months [95% CI, 2.3–3.2 months]; hazard ratio 0.32 [95% CI, 0.16–0.63]; P<0.001) (figure 1). Higher objective response rate (ORR) and disease control rate (DCR) were observed in TAE-iNKT patients (52% and 85%, respectively) compared with TAE patients (11% and 33%; respectively)(table 2). Five TAE-iNKT patients and 1 TAE patient achieved completed response (figure 3). Median time to deterioration in QoL was longer in TAE-iNKT patients (9.2 months [95% CI, 6.0–13.3 months]) compared with TAE patients (3.0 months [95% CI, 2.9–3.0 months]) (figure 2). The mean lymphocytes were higher in the TAE-iNKT group than in the TAE group at 8 (1.48 vs. 0.95×109/L, P=.007) and 12 (1.49 vs. 0.89×109/L, P=.001) weeks (figure 4). Grade 3 adverse events occurred in 1 TAE-iNKT patient (4%) and 5 TAE patients (19%). All other adverse events were grade 1–2(table 3).ConclusionsiNKT cell infusion significantly improved PFS, ORR, DCR, and QoL with manageable toxicity during TAE therapy in patients with HCC.AcknowledgementsThis study was funded by Capital Health Research and Development Projects (grant number: 2018-1-2181), the Original Exploration Program of the National Natural Science Foundation of China (grant number: 82150110), and the Beijing Municipal Administration of Hospitals Incubating Program (grant number: PX2019063). Nonfinancial support: iNKT cell was sponsored by the GeneKey GMP Lab.Trial RegistrationClinicalTrials.gov Identifier: NCT04011033ReferencesBray F, Ferlay J, Soerjomataram I, Siegel RL, Torre LA, Jemal A. Global cancer statistics 2018: GLOBOCAN estimates of incidence and mortality worldwide for 36 cancers in 185 countries. CA Cancer J Clin. Nov 2018;68(6):394−424.Lafaro KJ, Demirjian AN, Pawlik TM. Epidemiology of hepatocellular carcinoma. Surgical oncology clinics of North America. Jan 2015;24(1):1−17.Guidelines) NCPGiON. Hepatobiliary Cancers. National Comprehensive Cancer Network. 2020: Version 5. Fort Washington.Vogel A, Cervantes A, Chau I, et al. Hepatocellular carcinoma: ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up. Annals of oncology: official journal of the European Society for Medical Oncology. Oct 1 2018;29(Suppl 4): iv238−iv255.Kokudo N, Takemura N, Hasegawa K, et al. Clinical practice guidelines for hepatocellular carcinoma: The Japan Society of Hepatology 2017 (4th JSH-HCC guidelines) 2019 update. Hepatol Res. Oct 2019;49(10):1109−1113.Chang PY, Huang CC, Hung CH, et al. Multidisciplinary Taiwan Consensus Recommendations for the Use of DEBDOX-TACE in Hepatocellular Carcinoma Treatment. Liver Cancer. Oct 2018;7(4):312−322.Siegel RL, Miller KD, Jemal A. Cancer statistics, 2020. CA: a cancer journal for clinicians. Jan 2020;70(1):7−30.Gao Y, Guo J, Bao X, et al. Adoptive Transfer of Autologous Invariant Natural Killer T Cells as Immunotherapy for Advanced Hepatocellular Carcinoma: A Phase I Clinical Trial. Oncologist. Nov 2021;26(11): e1919−e1930.Ethics ApprovalThe study protocol and consent form were approved by the ethics committee of Beijing Youan Hospital (Jing You Ke Lun [2018] No. 016), and the other two participating units were subject to ethical examination and approval of the lead unit.ConsentWritten informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journalAbstract 593 Figure 1Abstract 593 Figure 2Abstract 593 Figure 3Abstract 593 Figure 4Abstract 593 Table 1Patient demographic and disease characteristicsAbstract 593 Table 2Response to autologous iNKT cell infusionAbstract 593 Table 3Adverse events